DETERMINANTS OF BANKING CREDIT IN THE BRAZILIAN ECONOMY: THE ROLE OF MICRO AND MACROECONOMIC FACTORS FROM 2001 TO 2012 - Almeida, Fernanda Dantas (2017)
The objective of this paper is to identify the major determinants of banking credit in the Brazilian economy, considering the influence of specific characteristics of the financial institutions and monetary policy. The empirical model is based on a theoretical approach of the credit channel in which banks decide on their loan supply taking into account the uncertain future monetary policy. The sample consists of a balanced panel, composed of 75 banks in the period 2001-2012. This paper contributes with the literature by showing that there was no relevant impact from the macroeconomic environment on the credit supply in the analyzed period. The government has adopted a countercyclical credit policy mismatched from prevailing macroeconomic conditions. In addition, the growth of credit granted to individuals, who are less sensitive to the macroeconomic environment, also contributed to the little influence of the monetary policy on the credit expansion. Moreover, the results illustrated the importance of the banks’ strategy, in addition to the inertial effect of the credit supply.